Habituasi Memberi Salam sebagai Strategi Pembentukan Karakter Sopan Santun Siswa di MAN 3 Aceh Besar - Cut Alfia Laina; Ainal Mardhiah; Rusydi Rusydi; Rafidhah Hanum (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to describe how the habituation of greeting functions as a strategic approach in shaping students’ polite character at MAN 3 Aceh Besar. Education is not solely focused on cognitive mastery but also carries a moral responsibility to cultivate noble character among students. In this context, greeting others represents a form of habituation with both spiritual and social value, as it conveys prayer, respect, and ethical conduct in interpersonal interactions. This research employed a qualitative approach with data collected through observation, interviews, and documentation involving the Islamic Ethics teacher and student activities within the school environment. The findings indicate that teachers implement structured planning and clear guidelines in reinforcing the practice of greeting, including modeling appropriate behavior, providing guidance, and continuously instilling the meaning of greetings. Consistent implementation of this habituation fosters a culture of mutual respect within the school. Its positive impact is reflected in students’ increased respectfulness, friendliness, and courtesy toward teachers, peers, and other school members. Thus, the habituation of greeting proves to be an effective strategy for strengthening character education based on Islamic values